2013
DOI: 10.1111/ijag.12046
|View full text |Cite
|
Sign up to set email alerts
|

Pattern Formation in Silicate Glass Corrosion Zones

Abstract: Alteration zones of archeological glasses often show intriguing lamellar patterns in backscattered electron images. Here, we report results of static glass corrosion experiments with two different silicate glasses that revealed laminar porosity and subordinately chemical patterns inside silica-based corrosion zones that resemble those seen in naturally altered, ancient glasses. Aside from common laminar patterns, more complex patterns were observed in corrosion zones that developed along a fracture network. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
55
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 53 publications
9
55
1
Order By: Relevance
“…1), the presence of which is commonly observed in similar experiments (e.g., Bunker et al, 1986;Casey and Bunker, 1990;Jégou et al, 2000;Donzel et al 2003;Dohmen et al, 2014). Experiments with glass "M", reacted in isotopically unlabelled milliQ water (18.2 MΩ·cm at 25 °C) at 90°C, contained etch pits after 1 hour (Fig.…”
Section: Resultssupporting
confidence: 60%
“…1), the presence of which is commonly observed in similar experiments (e.g., Bunker et al, 1986;Casey and Bunker, 1990;Jégou et al, 2000;Donzel et al 2003;Dohmen et al, 2014). Experiments with glass "M", reacted in isotopically unlabelled milliQ water (18.2 MΩ·cm at 25 °C) at 90°C, contained etch pits after 1 hour (Fig.…”
Section: Resultssupporting
confidence: 60%
“…Geisler and co-workers have suggested that banding in the alteration layers on the surface of glass can be explained by a self-organisation process involving coupled dissolution-reprecipitation on the surface of glass. 39,40 They argue that the underlying glass dissolution is congruent throughout, but that after the initial stage of dissolution, a silica gel layer develops and as this ripens, glass dissolution continues at the interface behind a silica gel layer. This model suggests that local compositional and pH changes occur in the pore solution that is present between the silica gel layer and the glass surface, and that diffusion of the species from the pore solution to the bulk solution is limited by the silica gel layer.…”
Section: Discussionmentioning
confidence: 99%
“…from the layers considered to be protective, and becomes a driving force that sustains glass dissolution. Another approach has been proposed these last years to revisit glass dissolution mechanisms (Geisler et al, 2010;Hellmann et al, 2012;Dohmen et al, 2013): the key processes are the congruent dissolution of the glass whatever the reaction progress and the leaching conditions and the in situ precipitation of the less soluble elements at the reaction front to form alteration products (gel, crystalline phases).…”
Section: Discussionmentioning
confidence: 99%